2006
DOI: 10.1038/sj.pcan.4500880
|View full text |Cite
|
Sign up to set email alerts
|

The changing pattern of management for hormone-refractory, metastatic prostate cancer

Abstract: Prostate cancer responds initially to hormonal manipulation by androgen withdrawal and peripheral androgen blockade. The inevitable progression to a hormone-refractory state is accompanied by an exacerbation of local symptoms and metastatic spread, principally to the bones, which has a considerable impact on quality of life and survival. Treatment of hormonerefractory prostate cancer is palliative, and surgery and radiotherapy are used for the relief of lower urinary tract symptoms and localized painful bony m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Bone pain in patients with prostate cancer indicates bone metastases and is one of the most common signs of metastatic disease progression or recurrence. 6 Consequently, the primary healthrelated quality of life (HRQL) impacts of metastatic prostate cancer are often attributed to bone metastases and resulting skeletal complications. 7 Commonly used measures of symptoms and HRQL in metastatic prostate cancer research are generic cancer HRQL instruments, including the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire C30 (QLQ-C30) and the Functional Assessment of Cancer TherapyeGeneral (FACT-G), which are often combined with the prostate cancerespecific module for the instrument, such as the EORTC QLQ-PR25 and the Functional Assessment of Cancer TherapyeProstate (FACT-P), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bone pain in patients with prostate cancer indicates bone metastases and is one of the most common signs of metastatic disease progression or recurrence. 6 Consequently, the primary healthrelated quality of life (HRQL) impacts of metastatic prostate cancer are often attributed to bone metastases and resulting skeletal complications. 7 Commonly used measures of symptoms and HRQL in metastatic prostate cancer research are generic cancer HRQL instruments, including the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire C30 (QLQ-C30) and the Functional Assessment of Cancer TherapyeGeneral (FACT-G), which are often combined with the prostate cancerespecific module for the instrument, such as the EORTC QLQ-PR25 and the Functional Assessment of Cancer TherapyeProstate (FACT-P), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This finding presents an opportunity for bone-seeking targeted therapy, such as Sr89, a beta-emitting radionuclide that selectively localizes in bone mineral at sites of active osteogenesis [16]. Sr89 has a palliative effect in ARPC patients [1][2][3], however, it does not improve the overall survival whether it is given alone or in combination with other chemotherapeutic agents such as doxorubicin [6,17] or cisplatin [5,18]. In a phase II randomized study, Tu et al [6] reported that Sr89 given in combination with doxorubicin as a consolidation treatment (following 2 cycles of induction regimen consisting of ketoconazole, doxorubicin, estramustine and vinblastine) improved the survival of a subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…It emits beta particles that lead to a palliative effect (pain relief and reduction in pathologic fractures) in androgen-resistant prostate cancer (ARPC) [1][2][3]. Enhancement of this palliative effect by combination with chemotherapy was reported in several phase II studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of metastatic cells in bone disrupts normal bone physiology and structure (3) and causes a range of serious complications, including pain, pathological fractures and spinal cord compression (2, 4). Current treatments with surgery, radiotherapy, chemotherapy and bisphosphonate administration may slow disease progression, but are associated with deleterious side effects (5) and are often not curative. In light of the above, new therapies for this disease are urgently needed.…”
mentioning
confidence: 99%